Holoseenin ajanlasku kvartäärigeologi Cesare Emilianin tapaan - Helama, Samuli (Suomen Geologinen Seura, 2019)
Cesare Emiliani (1922–1995) was a micropalaeontologist and Quaternary geologist who introduced isotopic stratigraphy to deep-sea studies and opened the way to quantitative studies of the history of climate and the ice ages. However, beyond these contributions, he was a renaissance scientist, familiar with classical languages, versed in history, with interests in tectonics, evolution, extinction and human impact on our planet, to name a few. A quarter century ago, Emiliani (1993, 1994) proposed a calendar reform that was supposed to renew our way to count years. This calendar has its starting point at the beginning of the Holocene and as a result has no obvious religious connotation. In particular, the new timeline (also known as the ‘Holocene calendar’ or ‘Human Era calendar’) was expected to benefit from simplifications concerning the BC/AD boundary. That is, the lack of year zero in our current calendar,which needs to be taken into account every time the time intervals are calculated over the boundary (for example, the distance between 1.5 BC and AD 1.5 equals only one year, not three years). Moreover, the numbers increase in opposite directions over the BC/AD boundary, whereas the time flows in the same direction. In Emiliani’s calendar reform the year 10,000 BC was set to 1. As a result, the years 1 BC and AD 1 would then become the years 10,000 and 10,001, respectively. Accordingly, we would today live the year 12,019. Interestingly, the reform results in a timeline that mimics the geochronology recovered from proglacial varve records from southern Finland, as it was originally set by Sauramo (1918, 1920). This varve record was based on a timeline where the zero year of the chronology was set to the varve expected to have been deposited at the end of the second Salpausselkä phase i.e. the base of the Holocene. Despite the obvious advantages, the calendar reform was also criticized by contemporaries, including geoscientists. More generally, Emiliani’s suggestion illustrates the difficulties inherent in trying to juxtapose the human calendar with the geological time.
Keywords: holoseeni; kronostratigrafia; isotooppigeokemia; millennium; geologia